β-Galactosidase from Kluyveromyces lactis: characterization, production, immobilization and applications - A review - Albuquerque, Tiago Lima de (2021)
A review on the enzyme β-galactosidase from Kluyveromyces lactis is presented, from the perspective of its structure and mechanisms of action, the main catalyzed reactions, the key factors influencing its activity, and selectivity, as well as the main techniques used for improving the biocatalyst functionality. Particular attention was given to the discussion of hydrolysis, transglycosylation, and galactosylation reactions, which are commonly mediated by this enzyme. In addition, the products generated from these processes were highlighted. Finally, biocatalyst improvement techniques are also discussed, such as enzyme immobilization and protein engineering. On these topics, the most recent immobilization strategies are presented, emphasizing processes that not only allow the recovery of the biocatalyst but also deliver enzymes that show better resistance to high temperatures, chemicals, and inhibitors. In addition, genetic engineering techniques to improve the catalytic properties of the β-galactosidases were reported. This review gathers information to allow the development of biocatalysts based on the β-galactosidase enzyme from K. lactis, aiming to improve existing bioprocesses or develop new ones.